Ground-penetrating radar and electrical resistivity tomography reveal a deep stratigraphic sequence at Mochena Borago Rockshelter, southwestern Ethiopia. (August 2019) - Lanzarone, Peter; Seidel, Marc; Brandt, Steven; Garrison, Ervan; Fisher, Erich C.
Abstract: Archaeological sites in rockshelter environments have long been noted to provide excellent preservation of cultural and stratigraphic deposits, encapsulating the past occupational history of inhabitants over time. Such sites in eastern Africa have shed light on the behavior of Homo sapiens during critical landmarks in evolutionary history. Mochena Borago is a large rockshelter located in southwest Ethiopia. The site contains a dense accumulation of flaked stone artifacts deposited in archaeological horizons that span Marine Isotope Stage 3 (MIS 3), a period where securely-dated sites are limited in the archaeological record. In this study, we present the results of a ground penetrating radar (GPR) and electrical resistivity tomography (ERT) survey. Due to complexities in the interpretation of sedimentary deposits observed in non-contiguous excavation areas, geophysical surveys were collected to image vertical and lateral variations in stratigraphy and depth to the basement as a proxy for total sediment thickness. Data were interpreted based on eleven distinct GPR facies, where three main facies are highlighted as they relate to irregular, erosional and depositional sedimentary processes. The facies describe mechanisms for sediment transport into the shelter as well as post-depositional processes. Geophysical data also indicate the presence of laterally extensive subsurface unconformities and evidence of a structured basement that has controlled sedimentary deposition over time. We conclude that the GPR and ERT data acquired at Mochena Borago illuminate subsurface stratigraphic boundaries, and aid in the interpretation of sedimentary packages across the site. Highlights: Mochena Borago is a large rockshelter in southwestern Ethiopia. GPR and ERT methods illuminate subsurface stratigraphic interfaces, this being one of the first combined studies in the region. Data are grouped into a facies classification based on depositional processes and reveal the evolution of stratigraphic deposits over time. A map of the top basement was created to guide future excavations.